In vivo production of a stable single-stranded cDNA in Saccharomyces cerevisiae by means of a bacterial retron. - Miyata, S (1992)
Gram-negative bacteria such as Myxococcus xanthus, Stigmatella aurantiaca, and Escherichia coli contain retroelements called retrons. Retrons consist of the msr-msd region and the gene for reverse transcriptase (RT), which are essential for the production of the branched RNA-linked ms-DNA (multicopy single-stranded DNA). In this study, we attempted to produce msDNA in the yeast Saccharomyces cerevisiae. Retron Ec67 from E. coli, which is responsible for the production of msDNA-Ec67, was cloned under the GAL10 promoter in a 2-microns-based plasmid. msDNA thus produced was detected by extending the 3' end of the msDNA by avian myeloblastosis virus RT. This yielded a main product of 117 nucleotides. Treatment of this product with RNase A resulted in a DNA of 105 nucleotides. These results are in good agreement with the structure of msDNA-Ec67. The production of msDNA-Ec67 was further confirmed by Southern blot hybridization. The msDNA production was dependent upon the bacterial RT gene in the clone and was increased severalfold when the RT gene of retron Ec67 was placed in front of the msr-msd region. The potential of msDNA as a eukaryotic vector producing a stable single-stranded DNA as well as RNA is discussed.